Induction of ABCA1 Expression Is Correlated With Increased CREB Phosphorylation and Altered Cytokine Secretion - Zaid, Maryam (Université d'Ottawa / University of Ottawa, 2011)
ABCA1 is believed to affect macrophage inflammatory responses, but the mechanism by which ABCA1 may impact cytokine secretion in macrophages has yet to be fully defined. We observed that the induction of ABCA1 expression in three different cell lines, namely BHK, RAW 264.7 macrophages, and primary bone marrow derived macrophages (BMDMs), results in a significant increase in phosphorylated CREB, a known protein kinase A (PKA) substrate. In RAW macrophages, induction of ABCA1 expression by the LXR-agonist T0901317 is correlated with a decrease in LPS-stimulated secretion of proinflammatory cytokines IL-6 and TNF-α. Additionally, the secretion of anti-inflammatory cytokine IL-10 was increased upon ABCA1 induction. A similar trend was observed in BMDMS: ABCA1-expressing BMDMs released less TNF-α and more IL-10 compared to ABCA1-knockout BMDMs. We speculated that the inflammation modulating effects of ABCA1 in macrophages could be a result of PKA activation. Indeed, we found that the LXR-induced ABCA1 phenotype can be mimicked by cAMP in macrophages. 8-bromo-cAMP, a PKA activator, dose-dependently suppressed inflammatory cytokine secretion while promoting IL-10 release in the absence of ABCA1 expression. Finally, we found that the T0901317-induced ABCA1 expression is correlated with higher expression levels of MKP-1, a downstream target of PKA known to suppress inflammatory responses. Together, our results suggest that ABCA1 expression may activate PKA and CREB and that such activation may contribute to the inflammatory modulating effects of ABCA1.
Keywords: ABCA1; atherosclerosis; LXR-agonist; CREB; MKP-1; PKA; inflammation